SOCIAL PREJUDICE IN TONI MORRISON’S THE BLUEST EYE - Nova Vertiwi Simamora; Bonar Gurning (Muse: Jurnal of Art, 2025)
This study explores social prejudice in Toni Morrison’s The Bluest Eye. The novel is seen as a portrait of social prejudice dealing with antilocution, avoidance, discrimination, physical attack, and extermination. This is a qualitative study; the primary data source is the novel The Bluest Eye, while secondary data are taken from books, journal articles, and relevant online sources. The analysis combines the literary sociology theory of Wellek and Warren, which sees that, literature is a reflection of social reality, and Gordon Allport’s concept of prejudice to analyze the causes and types of prejudice antilocution, avoidance, discrimination, physical attack, and extermination, shown in the novel. In conclusion, Toni Morrison in The Bluest Eye vividly conveys how social prejudice destroys a person’s identity and hope for life, especially those who are most vulnerable.